Colonialism and the Development of Markets on the Jos Plateau - Mohammed, Barira (Kashere Journal of Humanities, Management and Social Sciences, 2022)
A lot has been written about the establishment of colonial administration on the Jos Plateau with focus around the economic, social and political dimensions. What is however neglected is the history of marketplaces. This work thus examines the development of the colonial economy to unpack their ramifications within the context of market exchange on the Jos Plateau. This historicised approach will demonstrate the transformational force of the British colonial formation upon pre-colonial structures in the area.